Қазақ, ағылшын тілдеріндегі түр-түспен байланысты фразеологиялық тіркестердің қолданылуы және орыс тіліне аударылу ерекшеліктері - Сақау, А.; Волоха, А. (My University, 2013)
This article considers the particularities of translation of English phrase logical units into Kazakh language. The phrase logical units can change their meanings by translation and can be used.